The Effect of Promotion and Hedonic Shopping On Impulse Buying On Spotify Applications : (Study on Students of the Faculty of Economics and Business Class of 2018-2021 University Buana Perjuangan Karawang) - Janter Sihombing; Aji Tuhagana; Dexi Triadinda (Neo Journal of economy and social humanities, 2022)
Music streaming platforms are currently undergoing systematic updates due to newcomer music streaming applications that have emerged with the latest innovations. In Indonesia, there are many music streaming applications that are very familiar, namely Spotify, Resso, Music Player, and Jooks. The increase in the use of spotify, from 2017 to 2021 is always increasing. However, with the high number of downloads, spotify has a lower rating than the Resso and Joox applications. The research method used by the researcher is a quantitative research method with a causal study. The population for this research is Management Students, Faculty of Economics and Business, University of Buana Perjuangan Karawang Class of 2018-2022. The sampling technique in this study is purposive sampling with the Lemeshow formula, the number of samples obtained is 100 respondents. The analysis used is PLS SEM analysis. Based on the results of the study, it was found that the promotion variable and the hedonic shopping variable had a positive and significant effect on the impulse buying variable on the Spotify Music Streaming application.